Study on the Effect of Flocculation and Sedimentation on the Mechanical Properties of Iron Tailing Sand - Yuping Xu; Chunliu Wang; Jingyuan Liu; Xiuwei Chai (Advances in Civil Engineering)
Tailings sand is the dam-building material of the tailings dam accumulation sub-dam, and its mechanical properties directly affect the safety and stability of the whole tailings dam. With the improvement of mineral sorting technology, the content of fine and ultrafine particles in the tailings gradually increases, which will affect the mechanical strength of tailings accumulation sub-dam. To improve the settling effect of tailings accumulation in the Chengchao iron ore mine (China), the effect of iron tailings flocculation and settling law on the mechanical properties of tailings sand was studied. Polymerized iron sulfate (PFS) as an inorganic polymer flocculant, compared with the traditional flocculant, has a stronger flocculation and adsorption capacity, is widely used in drinking water, industrial wastewater, and domestic sewage treatment, is an anionic polyacrylamide (APAM-800) for polymer compounds, mainly divided into nonionic, cationic, and anionic three, and is commonly used mine flocculant at home and abroad. Through different flocculants, PFS, and APAM-800 compound flocculation and settling experiments, the effect of the flocculant-dosing scheme on the settling rate and turbidity of clarified liquid was determined, and the change in tailings consolidation shear strength of the best dosing scheme was measured. The experimental results showed that the settling rate of iron tailings was the fastest when PFS was used in combination with APAM-800 at 1.2 g L−1 and 0.20 g·L−1 dosages, respectively. The direct shear test results showed that the internal friction angle of tailings sand increased by 2.18°, the cohesion increased by 5.814 kPa, and the shear resistance of flocculated settled tailings increased, which can effectively improve the safety factor of tailings sand pile sub-dam.